Impurity Analysis and Microstructure Along the Climatic Transition From MIS 6 Into 5e in the EDML Ice Core Using Cryo-Raman Microscopy - Eichler, Jan; Weikusat, Christian; Wegner, Anna; Twarloh, Birthe; Behrens, Melanie; Fischer, Hubertus; Hörhold, Maria; Jansen, Daniela; Kipfstuhl, Sepp; Ruth, Urs; Wilhelms, Frank; Weikusat, Ilka (Frontiers in Earth Science, 2019)
Impurities in polar ice cores have been studied so far mainly for the purpose of reconstructions of past atmospheric aerosol concentrations. However, impurities also critically influence physical properties of the ice matrix itself. To improve the data basis regarding the in-situ form of incorporation and spatial distribution of impurities in ice we used micro-cryo-Raman spectroscopy to identify the location, phase and composition of micrometer-sized inclusions in natural ice samples around the transition from marine isotope stage (MIS) 6 into 5e in the EDML ice core. The combination of Raman results with ice-microsctructure measurements and complementary impurity data provided by the standard analytical methods (IC, CFA and DEP) allows for a more interdisciplinary approach interconnecting ice core chemistry and ice core physics. While the interglacial samples were dominated by sulfate salts - mainly gypsum, sodium sulfate (possibly thenardite) and iron-potassium sulfate (likely jarosite) - the glacial ice contained high numbers of mineral dust particles - in particular quartz, mica, feldspar, anatase, hematite and carbonaceous particles (black carbon). We cannot confirm cumulation of impurities in the grain boundary network as reported by other studies, neither micro-particles being dragged by migrating grain boundaries nor in form of liquid veins in triple junctions. We argue that mixing of impurities on millimeter scale and chemical reactions are facilitated by the deforming ice matrix. We review possible effects of impurities on physical properties of ice, however the ultimate identification of the deformation agent and the mechanism behind remains challenging.